Focus group discussion on factors for development of somatosensory games on hand function training for self-care ability of children with autism - Li, Ziming; Ramli, Saiful Hasley; Romli, Muhammad Hibatullah; Ahmad Azmeer, Raja; Sulaiman, Puteri Suhaiza; Lin, Chaoxin; Fei, Bingxue; Chu, Qingqing; Yu, Xinxin; You, Donggui (Taylor and Francis, 2024)
Objectives: This paper aims to identify factors for designing somatosensory games targeting hand function, explicitly focusing on eating behavior in children with autism spectrum disorder. Methods: A qualitative research methodology was used in the form of a focus group discussion, which was coordinated by a consortium consisting of parents of children with autism, therapists, and game designers. Results: The discussion explored factors influencing hand function and self-care in autistic children and design directions for using somatosensory games to improve hand function and eating skills. The results identified several themes: education, manifestation factors, performance, cognition, and game design. Conclusions: The findings underscore the importance of considering multiple aspects, such as motor, cognitive, and social abilities, when designing comprehensive assistance frameworks for autistic children. The proposed factors provide insights for designing effective and user-friendly somatosensory games to enhance hand function and self-care abilities in autistic children. The study contributes to understanding hand function training and self-care interventions in the context of ASD, bridging the gap between research and design in somatosensory game development. © 2024 The British Society of Developmental Disabilities.